Urban type of tourism: the role and importance in the modern tourist industry - Duissembayev, A.A.; Oralbaeva, A.K.; Omarkozhayeva, A.N.; Podsukhina, O.V. (BUKETOV BUSINESS REVIEW, 2017)
In the article was considered the urban view of tourism as the factor promoting social and economic developments, not only the certain city, but near regions. In the article the value and role of the international tourist exchanges is shown, tourist services in the context of international trade are considered, the tourism role in economy of the certain countries and a share of the sphere of tourist services in GDP of the certain state is shown. The definitions of city tourism as a modern phenomenon is considered. Opinions of theorists in the field of tourism. Several determinations of new types of tourism to Kazakhstan are considered. There were researched the network between city attractions, cultural-historic resources, the degree of infrastructure development and the opportunities of development in the city different types of tourism such as: city tourism, business, cultural heritage etc. The role of the world cities in tourist production is studied from the point of historic retrospectives. Particularly, some statistical data on development of city tourism, both in the world in general, and in the country are analysed. Examples of holding global events on capital platforms are given. Some indicators of touristic production in capital city is studied. The results on further formation of Astana as a center of touristic events are summed up, based on world practice and future world format events in the city.